A proposal of system for device capability assessment in bring your own device (BYOD) environment of computer assisted personal interviewing - Rosnah, Aditya Abdulmunaf; Anang, Yunarso (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2018)
Statistics Indonesia, known in Indonesia as Badan Pusat Statistik (BPS), has conducted a series of trials to utilize Computer-Assisted Personal Interview (CAPI) in a census or survey. However, CAPI costs a lot of money to procure and maintain the device. Bring Your Own Device (BYOD) principle offers cost opportunity to device management. In the practice of BYOD in BPS, a device that has good performance is required, because some devices aren’t capable of running CAPI properly. Yet, in BPS there is no standard value to qualify mobile devices to be used in census or survey. Therefore, it is necessary to review what kind of device is suitable for using CAPI. This study utilized CAPI used in a student’s field study as a case study reference. Initially, researchers develop benchmark applications as a tool for feasibility. Furthermore, developed application is tested on a certain base device to calculate the scores to be used as the standard values.